Respiratory syncytial virus infections in pediatric transplant recipients: A Canadian Paediatric Surveillance Program study. (7th July 2015) - Robinson, Joan L.; Grenier, Danielle; MacLusky, Ian; Allen, Upton D.
Abstract The incidence and spectrum of severity of RSV infections in SOT or HSCT recipients is not known. From September 2010 through August 2013, pediatricians were surveyed monthly by the CPSP for SOT or HSCT recipients with RSV infection within two yr post‐transplant. There were 24 completed case report forms that fit the inclusion criteria (10 HSCT and 14 SOT recipients). Six of 24 cases (25%) remained outpatients, and 11 (46%) were managed on an inpatient ward, while seven (29%) required intensive care of which five required mechanical ventilation and two died of RSV infection. Ten of 23 cases (43%) were nosocomial with these data not recorded for one case. Many transplant recipients recover uneventfully from RSV infection in the first two yr post‐transplant. However, severe disease and death also occur. Larger studies are required to establish risk factors for poor outcomes. Prevention of nosocomial RSV should be a priority in transplant recipients.